NCMP-13. LEPTOMENINGEAL DISEASE FOLLOWING RESECTION OF INTRAVENTRICULAR MELANOMA METASTASIS DIAGNOSED THROUGH CIRCULATING TUMOR CELLS. (9th November 2020) - Wang, Christopher; Limia, Melissa; Forsyth, Peter; Liu, James
Abstract: Leptomeningeal disease in the setting of malignant melanoma metastatic to the brain provides a dismal prognosis. The relationship between intraventricular metastatic tumor seeding following surgical resection and development of leptomeningeal disease (LMD) is not completely clear, although there appears to be correlation. While the mechanisms that drive the development of LMD is not well understood, monitoring of cerebrospinal fluid (CSF) for circulating tumor cells (CTCs) in high risk patients may allow for early intervention for LMD prior to radiographical diagnosis. This report describes a patient with metastatic melanoma who developed ventricular trapping from an intraventricular melanoma metastasis. The patient underwent endoscopic assisted resection of the tumor. Due to concern for leptomeningeal seeding given the location of the tumor and use of surgical resection, CSF analysis was performed. CTC count was increased shortly after surgical resection along with cytology that was suspicious for malignancy. Due to the increase in CTCs, the patient was treated for LMD with whole brain radiation therapy and intrathecal pembrolizumab. Subsequent CSF analysis revealed clearing of malignant cells in the CSF. The patient developed symptoms consistent with LMD approximately 9 months after the surgery and died 21 months after resection of his brain metastasis. This case illustrates a rare occurrence of an intraventricular melanoma metastasis, and the use of CTC presence within the CSF to diagnose LMD for early intervention. This emphasizes that the risk of developing LMD must be considered with intraventricular metastasis or ventricular exposure during tumor resection, and that CTCs may be an effective factor to monitor for early development of disease with possible prolonged survival benefit.